Histamine-treated dendritic cells improve recruitment of type 2 CD8 T cells in the lungs of allergic mice - Amaral, María Marta (2010)
Histamine controls the function of dendritic cells (DCs). It appears to be required for the normal development of DCs. It also induces the chemotaxis of immature DCs and promotes the differentiation of CD4+ T cells into cells with a T helper type 2 (Th2) profile. Moreover, we have recently shown that histamine stimulates both the uptake and the cross-presentation of antigens by DCs, supporting the theory that histamine promotes activation of CD8 + T cells during the development of allergic pathologies. Here, we investigated whether the course of an allergic response, in a well-defined model of ovalbumin (OVA)-induced allergic airway inflammation, could be modulated by intratracheal injection of OVA-pulsed DCs previously treated with histamine (DCHISs). Compared with control DCs, DCHISs induced: (i) greater recruitment of CD8+ T cells in the lung, (ii) greater stimulation of the production of interleukin (IL)-5 by lung CD8+ T cells, and (iii) increased recruitment of CD11c/CD8 double-positive DCs in the lungs of allergic mice. Moreover, mice treated with DCHISs showed increased levels of serum-specific immunoglobulin E (IgE) antibodies directed to OVA, and a higher proportion of eosinophils in bronchoalveolar lavage (BAL) compared with mice treated with OVA-pulsed control DCs. Our results support the notion that histamine, by acting on DCs, increases the severity of allergic processes. © 2010 Blackwell Publishing Ltd.